ChemInform Abstract: An Efficient and Green Synthesis of Flavones Using Natural Organic Acids as Promoter under Solvent‐Free Condition. Issue 13 (March 2015) - Thorat, Nitin M.; Kote, Santosh R.; Thopate, Shankar R.
Abstract Naturally occurring acids are used as environmentally‐friendly acid catalyst in the synthesis of flavones (II) by cyclodehydration of 1‐(2‐hydroxyphenyl)‐3‐aryl‐1, 3‐propanediones (I).